Fresno-Merced Counties Legal Services Christmas Party at Patience Milrod's Home - Watkins, Howard::::::::: (1980)
Patience Milrod, Jasso Mendez, Marilyn Williams, Leroy Cordova, ? all laughing 3400 Block of E. Montecito Avenue